2022
DOI: 10.1039/d2sm00518b
|View full text |Cite
|
Sign up to set email alerts
|

Single atoms and small clusters of atoms may accompany Au and Pd dendrimer-encapsulated nanoparticles

Abstract: Au and Pd dendrimer-encapsulated nanoparticles (DENs) were characterized using aberration-corrected scanning transmission electron microscopy and energy dispersive spectroscopy. The results revealed single atoms and small clusters alongside the DENs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…It was also demonstrated that curcumin-conjugated bimetallic DENs can be selectively taken up by microglial cells in the brain, suggesting that they may be beneficial in the treatment of brain cancer [ 128 ]. Additionally, recent research has demonstrated that bimetallic DENs are capable of serving as miRNA carriers [ 23 , 129 , 130 , 131 ]. Intravenously injected Au–Pd DENs were also able to deliver miRNA to EGFR-expressing cancer tissues [ 132 ].…”
Section: Dendrimers and Inorganic Nanoparticlesmentioning
confidence: 99%
“…It was also demonstrated that curcumin-conjugated bimetallic DENs can be selectively taken up by microglial cells in the brain, suggesting that they may be beneficial in the treatment of brain cancer [ 128 ]. Additionally, recent research has demonstrated that bimetallic DENs are capable of serving as miRNA carriers [ 23 , 129 , 130 , 131 ]. Intravenously injected Au–Pd DENs were also able to deliver miRNA to EGFR-expressing cancer tissues [ 132 ].…”
Section: Dendrimers and Inorganic Nanoparticlesmentioning
confidence: 99%
“…9 (a) Absorption and photoluminescence (PL) spectra of pyrene core-dendrimer (10). (b) Fluorescence behavior of pyrene-amine-containing dendrimer (11).…”
Section: Pyrene-based Dendrimersmentioning
confidence: 99%
“…(b) Structure of amphiphilic dendrimers (15). addition, the 1,4,7,10-tetraazacyclododecane (cyclen) unit of a pyrene-based dendrimer (11) was studied using steady-state uorescence and single-photon counting uorescence. Pyrenelabeled signals from the molecules were recorded in each solvent and showed the expected uorescence spectra.…”
Section: Pyrene-based Dendrimersmentioning
confidence: 99%
See 2 more Smart Citations